MURABAHAH FINANCING AND EFFECT ON EARNINGS IJARAH BCA ISLAMIC YEAR 2012-2015 - Agus Arwani; Muhammad Wakhidin (Jurnal Ekonomi dan Bisnis Islam | Journal of Islamic Economics and Business, 2018)
Financing as an important element in the bank. Based on data from Bank Indonesia, the loan product most in demand is Murabaha, which is financed with the principle of buying and selling. The purpose of this study was to determine the effect of the Murabahah and Ijarah partially and simultaneously to profit BCA Syariah years 2012-2015. This type of research correlation with a quantitative approach.The data source of monthly financial reports from January 2012 to December of 2015. The analysis of the data by t-test  indicates that the variable Murabaha financing with significant influence on profits of less than 5% is equal to 0,000 and for Ijarah variable has no effect on earnings by more than 5% significance that is equal to 0.374. Based on the test results F it can be concluded that the financing Murabaha and Ijarah effect on profits, it is based on the calculation of the value of the F test of significance smaller than the significance level of 5% IE 0,000. The ability to predict the independent variable on the dependent variable is equal to 59.1% is indicated by the Adjusted R Square of 59.1%, while the remaining 40.9% is influenced by other variables.Keywords: Earnings, Murabahah, Ijarah